2007
DOI: 10.1093/humrep/del487
|View full text |Cite
|
Sign up to set email alerts
|

Follicle growth is inhibited by benzo-[a]-pyrene, at concentrations representative of human exposure, in an isolated rat follicle culture assay

Abstract: Our data suggest that B[a]P, at levels representative of those measured in human FF, may adversely affect follicle development and be an ovarian toxicant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 28 publications
3
70
0
3
Order By: Relevance
“…Rat ovarian follicles have been explanted and cultured in vitro (isolated rat follicle culture) (Neal et al, 2007). This assay involves isolating 80 to 100 lm diameter follicles from ovaries, treating them in vitro with test compounds, and measuring the effect on follicle growth.…”
Section: Ovarian Follicular Explantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat ovarian follicles have been explanted and cultured in vitro (isolated rat follicle culture) (Neal et al, 2007). This assay involves isolating 80 to 100 lm diameter follicles from ovaries, treating them in vitro with test compounds, and measuring the effect on follicle growth.…”
Section: Ovarian Follicular Explantsmentioning
confidence: 99%
“…This assay involves isolating 80 to 100 lm diameter follicles from ovaries, treating them in vitro with test compounds, and measuring the effect on follicle growth. This assay was used to show that benzo-[a]-pyrene, a PAH in cigarette smoke, inhibits FSH stimulated follicular growth dose dependently (Neal et al, 2007). In this study, the concentrations of benzo-[a]-pyrene were also measured in the serum and follicular fluid of smoking and nonsmoking women undergoing in vitro fertilization procedures.…”
Section: Ovarian Follicular Explantsmentioning
confidence: 99%
“…Cigarette smoke condensate (CSC) has been used to simulate smoking, and in ovariectomized rats CSC (10 or 20 mg/kg body weight) increased uterine wet weight and induced P receptor expression in the uterus and mammary gland (33). Cigarette smoke condensate is derived from the particulate phase of cigarette smoke and is composed of compounds such as nicotine, phenol, anthracyclic hydrocarbons, nitrosamines, and trace metals such as cadmium (34).In our previous in vitro study (31), 5-day exposure (short-term culture) of isolated rat follicles to benzo[a]pyrene (B[a]P), an important component of cigarette smoke, resulted in decreased growth and E 2 output. We subsequently used a 13-day isolated mouse follicle culture system (long-term culture) to demonstrate that B[a]P exposure delayed antral follicle development and decreased E 2 output and follicle survival (32).…”
mentioning
confidence: 99%
“…Oviductal function was differentially inhibited by individual components of cigarette smoke and whole cigarette smoke in hamsters (28). Cigarette smoke contains >4,000 chemicals (29), some of which are toxic to ovarian follicles (4,(30)(31)(32). Cigarette smoke condensate (CSC) has been used to simulate smoking, and in ovariectomized rats CSC (10 or 20 mg/kg body weight) increased uterine wet weight and induced P receptor expression in the uterus and mammary gland (33).…”
mentioning
confidence: 99%
“…Decreased follicular levels of 17 β -estradiol were observed in smoking women when compared with nonsmokers, and cultured human granulosa cells were reported to secrete decreased amounts of 17 β -estradiol in the presence of an extract of cigarette smoke (VanVoorhis et al , 1992 ). In a study of females undergoing IVF, increased levels of the PAH, BaP, were found in serum and follicular fl uid in those who were smokers, and this was associated with lower rates of implantation and successful pregnancies compared with control nonsmoking women (Neal et al , 2007 ). Thus, these effects may relate to the infertility associated with cigarette smoking.…”
Section: Translational Applicationsmentioning
confidence: 99%